MAIN PREDICTORS OF TRAUMATIC RECURRENT INTRACRANIAL HEMATOMAS (Modern American Journal of Medical and Health Sciences, 2026)
Were analyzed the treatment outcomes of 28 patients with recurrent intracranial hematomas. Was carried out during the study, the main predictors and terms of formation of recurrent hematomas were determined and the assessment of treatment outcomes. Recurrent intracranial hematomas are among the complications of the early postoperative period, since their development is accompanied by high lethality, deterioration of functional results of treatment and an increase in the duration of hospital stay of patients.